DESIGN OF GROUP COUNSELING INTERVENTION WITH RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) TECHNIQUES TO REDUCE STUDENT'S AGRESSIVE BEHAVIOR - Budiyanto; Salsabila, Nabila Salma; Purwoko, Budi; Hariastuti, Retno Tri (CV. TOTUS TUUS, 2023)
Behavior aggressive in teenagers is phenomenon that requires attention quick for handled so as not give bad impact good for individual nor other people. Study this have destination for make design intervention counseling group with REBT (Rational Emotive Behavior Therapy) technique in reduce behavior aggressive. Study this use method studies literature with display results study appropriate past _ with variable discussion. Study results literature this explain two points related: 1) method counseling group with REBT technique in handle behavior aggressive youth, and (2) design intervention counseling group with REBT technique.